2020
DOI: 10.1128/mbio.01247-20
|View full text |Cite
|
Sign up to set email alerts
|

Roles of ATP Hydrolysis by FtsEX and Interaction with FtsA in Regulation of Septal Peptidoglycan Synthesis and Hydrolysis

Abstract: ABSTRACT In Escherichia coli, FtsEX coordinates peptidoglycan (PG) synthesis and hydrolysis at the septum. It acts on FtsA in the cytoplasm to promote recruitment of septal PG synthetases and recruits EnvC, an activator of septal PG hydrolases, in the periplasm. Following recruitment, ATP hydrolysis by FtsEX is thought to regulate both PG synthesis and hydrolysis, but how it does this is not well understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 44 publications
(37 reference statements)
1
26
0
Order By: Relevance
“…In support of this, mutations in the ECL4 of RodA and in the pedestal domain of PBP2 activate the complex (14,16). Similarly, here we found that mutations in the ECL4 of FtsW can lock the protein in an inactive state (M269K) that no longer 22 responds to the activation of FtsN or in an active state (E289G and to a less extent M269I) that no longer requires FtsN for division. Mutations in the pedestal domain of FtsI can also activate (K211I) or inactivate (G57D, S61F, L62P and R210C) the FtsWI complex in vivo.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In support of this, mutations in the ECL4 of RodA and in the pedestal domain of PBP2 activate the complex (14,16). Similarly, here we found that mutations in the ECL4 of FtsW can lock the protein in an inactive state (M269K) that no longer 22 responds to the activation of FtsN or in an active state (E289G and to a less extent M269I) that no longer requires FtsN for division. Mutations in the pedestal domain of FtsI can also activate (K211I) or inactivate (G57D, S61F, L62P and R210C) the FtsWI complex in vivo.…”
Section: Discussionsupporting
confidence: 77%
“…To prove that FtsW E289G and FtsI K211I were active division mutants, we tested if they suppressed other mutations that blocked septal PG synthesis. First, we tested the ATPase defective mutant of FtsEX, FtsE D162N X, which was previously shown to block septal PG synthesis and to be suppressed by FtsW M269I (19,22,32). As shown in Fig.…”
Section: Isolation Of Ftsw E289g and Ftsi K221i As Hyperactive Divisimentioning
confidence: 99%
“…Although FtsI is sufficient for the PG glycosyltranferase activity of FtsW in vitro [3], this appears to be a basal activity and another layer of regulation exists in vivo. This layer includes FtsA, FtsEX, FtsQLB, and FtsN (Fig 1B ) with FtsN arriving last and triggering FtsWI activity [18][19][20][21][22][23][24][25]. FtsN is a bitopic membrane protein with a short N-terminal cytoplasmic domain (FtsN cyto ), a transmembrane segment, followed by an essential domain (FtsN E ) and a SPOR domain in the periplasm [26].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Several proteins have been suggested to interact directly with FtsA to potentially modify the polymerization state, including ZipA, FtsN, and FtsEX [14,16,17,45,63]; all have been suggested to destabilize or bypass FtsA-FtsA interactions. Interestingly, FtsA is highly conserved indicating that the ATP hydrolysis and polymerization functions of FtsA have been evolutionarily preserved and are therefore critical for function [46].…”
Section: Discussionmentioning
confidence: 99%
“…We predict that other cell division proteins, such as ZipA or FtsEX may contribute to regulating the FtsA polymerization state [17,[43][44][45]. Once recruited by FtsA, FtsN would then activate FtsQBL and FtsWI for cell wall synthesis [18,45].…”
Section: Several Models Have Been Proposed To Resolve the Precise Indmentioning
confidence: 99%